2016
DOI: 10.1128/cvi.00078-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Novel HISCL Chemiluminescence Enzyme Immunoassay for Laboratory Screening of Hepatitis C Virus

Abstract: The hepatitis C virus (HCV) antibody assay remains the first-line screening test to identify HCV infection. The newly arrived HISCL Anti-HCV assay had a satisfactory seroconversion sensitivity. Its sensitivity and specificity were 98.97 and 100% for clinical samples. In general, the HISCL Anti-HCV assay may be a novel choice for clinical HCV screening.A bout 2.8% of the world population has been infected with the hepatitis C virus (HCV), and it causes Ͼ350,000 deaths annually, but most people are unaware of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Similar data on sensitivity and specificity of HISCL was reported by An et al(17). Elecsys anti-HCV II assay showed a sensitivity of 100% and a specificity of 99.66% in 7,726 routine samples from the Asia-Pacific region(18), while research by Feng et al(19) revealed that HISCL anti-HCV assay had a sensitivity of 98.97% and specificity of 100% in 1,048 samples from China. Other studies also indicated that both Elecsys and HISCL had superior performance in the detection of HBsAg and HIV…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Similar data on sensitivity and specificity of HISCL was reported by An et al(17). Elecsys anti-HCV II assay showed a sensitivity of 100% and a specificity of 99.66% in 7,726 routine samples from the Asia-Pacific region(18), while research by Feng et al(19) revealed that HISCL anti-HCV assay had a sensitivity of 98.97% and specificity of 100% in 1,048 samples from China. Other studies also indicated that both Elecsys and HISCL had superior performance in the detection of HBsAg and HIV…”
supporting
confidence: 76%
“…Results of seroconversion panel tests demonstrated that Elecsys had a slightly better performance than HISCL in early detection of all pathogen markers except for anti-HCV. Interestingly, Feng et al (19) compared anti-HCV assays of these two systems and found that Elecsys had a superior seroconversion sensitivity to HISCL (detection rate: 64.62% for Elecsys and 46.15% for HISCL). This advantage may be explained by the difference between ECLIA and CLIA in the detection mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This study describes a novel quantitative assay using a fully automated immunochemistry analyzer that employs chemiluminescence enzyme immunoassay (CLEIA) methodology 28 , 29 , HISCL (Sysmex Corporation, Kobe, Japan), to simultaneously detect IgG and IgM antibodies against two SARS-CoV-2 antigens, the spike (S) protein and the nucleocapsid (N) protein (N-IgG, S-IgG, N-IgM, and S-IgM). HISCL is widely used in several clinical fields due to its rapid reaction (17 min), wide dynamic ranges, and high reproducibility compared with standard enzyme-linked immunosorbent assay (ELISA).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 13 anti-HCV detection kits were enrolled: ARCHITECT Anti-HCV (ARCHITECT-Ab; Abbott Japan, Tokyo, Japan) (Yoo et al, 2015;Shepherd et al, 2020;Nam et al, 2021), Alinity i Anti-HCV (Alinity-Ab; Abbott Japan) (Shepherd et al, 2020;Nam et al, 2021), Lumipulse HCV (Lumipulse-Ab; Fujirebio, Tokyo, Japan), Lumipulse Presto HCV (Lumipulse Presto-Ab; Fujirebio), Lumipulse II Ortho HCV (Ortho-Ab; Fujirebio), Lumipulse Presto Ortho HCV (Ortho Presto-Ab; Fujirebio), Elecsys Anti-HCV II (Elecsys-Ab; Roche Diagnostics, Tokyo, Japan) (Yoo et al, 2015;Feng et al, 2016;Xu et al, 2019), Accuraseed HCV [II], (Accuraseed-Ab; Sanyo Chemical Industries, Kyoto, Japan), ADVIA Centaur anti-HCV assay (Centaur-Ab; Siemens Healthcare Diagnostics, Tokyo, Japan) (Dwyer, 2004;Yoo et al, 2015), HISCL Anti-HCV Assay Kit (HISCL-Ab; Sysmex, Kobe, Japan) (Feng et al, 2016), HISCL Anti-HCV II Assay Kit (HISCL II-Ab; Sysmex) (Xu et al, 2019), CL AIA-PACK HCVAb (CL AIA-Ab; TOSOH, Tokyo, Japan), and E Test 'TOSOH' II HCVAb (AIA-Ab; TOSOH). Of these anti-HCV detection kits, Lumipulse-Ab, Lumipulse Presto-Ab, Ortho-Ab, Ortho Presto-Ab, Accuraseed-Ab, HISCL-Ab, and CL AIA-Ab provide classification titers.…”
Section: Evaluation Of Hcv Detection Kitsmentioning
confidence: 99%